Prion Diseases - Gideon Informatics, Inc (Gideon Informatics, Incorporated, 2022)
Prion Diseases: Global Status is one in a series of GIDEON ebooks which explore all individual infectious diseases, drugs, vaccines, outbreaks, surveys and pathogens in every country of the world. Data are based on the GIDEON web application (www.gideononline.com) which relies on standard text books, peer-review journals, Health Ministry reports and ProMED, supplemented by an ongoing exhaustive search of the medical literature.